TRANSFROMASI PENDIDIKAN INDONESIA MELALUI PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Lutfiah Dwi Sari Berutu; Moza Nabilah Putri; Nabila Sukria Nasution; Nova Putri Elisa; Devi Rahma Aulia; Salma Sakina; Syakila Putri Murdani; Anisa Anisa; Thohirul Qolbi; Ahmad Khusein; Ere Mardella Arbiani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to examine the use of Information and Communication Technology (ICT) in supporting educational transformation in Indonesia. The development of ICT has brought significant changes to the learning process, in terms of methods, media, and communication between educators and students. This study uses a literature review method by collecting data from various literature sources such as scientific journals, books, and academic articles relevant to the research topic. The results of the study show that the use of ICT has a positive impact on improving the quality and effectiveness of learning, expanding access to education, and encouraging digital-based learning innovation. ICT also plays a role in creating more interactive, flexible, and learner-centered learning. However, the use of ICT also faces a number of challenges, such as unequal access to technology, limited digital competence of educators and students, disruption of learning concentration, and potential dependence on technology. Therefore, strategic efforts are needed in the form of equitable ICT infrastructure, increased digital literacy, development of quality digital learning content, and strengthening cooperation between the government, educational institutions, and the community. With proper management, ICT can be an important factor in realizing a modern, inclusive, and sustainable education system in Indonesia.